Invariant natural killer T‐cell neutralization is a possible novel therapy for human eosinophilic esophagitis. Issue 1 (10th January 2014) - Rayapudi, Madhavi; Rajavelu, Priya; Zhu, Xiang; Kaul, Ajay; Niranjan, Rituraj; Dynda, Scott; Mishra, Akanksha; Mattner, Jochen; Zaidi, Asifa; Dutt, Parmesh; Mishra, Anil
Abstract : Eosinophilic esophagitis (EoE) is a recently recognized inflammatory disorder that needs a potential therapeutic strategy. We earlier showed that iNKT cell‐deficient mice are protected from allergen‐induced EoE. Therefore, we now tested the hypothesis that iNKT cells are induced in the human EoE and is a novel possible target for the treatment of human EoE. Accordingly, we examine number of iNKT cells and eosinophils and expression of iNKT‐associated cell surface receptors and chemokines by performing immunofluorescence, qPCR and ELISA in the esophageal biopsies and blood samples of normal subjects (comparison control) and EoE patients. Herein, we show that iNKT cell number, their receptor subcomponents Vα24 and Vβ11 expression, and associated chemokine CXCL16 levels (or expression) are induced significantly in EoE patients compared with normal individuals. In addition, we show that CXCL16 levels (or expression) correlate with the mRNA levels of Vα24 receptor but not well with esophageal eosinophilia in human EoE. Of note, we show that in vivo activation of iNKT cells is sufficient to induce EoE in mice. Furthermore, we show that anti‐mCD1d‐ and anti‐hVα24Jα18‐neutralizing antibody treatment protects allergen‐induced experimental EoE. Taken together, we have shown first time that iNKT cells have a critical pathogenic role in human and experimental EoE. iNKT cell neutralization by humanized anti‐CD1d and anti‐Vα24Jα18 antibodies might be a novel and potential therapy for human EoE. Allergy: Fighting food‐fuelled inflammation: Immune cells belonging to the subset responsible for food allergy‐associated inflammation offers promising targets for potential therapeutics. Patients suffering from the painful symptoms of eosinophilic esophagitis (EoE) have few options except for dietary modification. Researchers led by Anil Mishra at Tulane University, USA, have identified a prominent role for innate natural killer T (iNKT) cells in EoE, thereby uncovering signaling pathways that might be blocked to halt this condition. The team observed greatly increased recruitment of iNKT cells in esophageal biopsies from EoE patients, and showed that EoE‐like symptoms can no longer be induced in mice that lack these cells specifically. Importantly, iNKT function depends on certain cell‐surface proteins that can be effectively blocked by existing antibodies. Mishra and colleagues demonstrated that these antibodies prevent allergen‐induced EoE in mice, and might therefore confer similar protection in humans.